A history of the modern Middle East rulers, rebels, and rogues - Anderson, Betty S. (Stanford University Press, 2016)
The textbook focuses on Turkey, Iran, and the Arab countries of the Middle East, as well as areas often left out of Middle East history-such as the Balkans and the changing roles that Western forces have played in the region for centuries-to discuss the larger contexts and influences on the region's cultural and political development. A History of the Modern Middle East highlights the complexity and variation of the region, countering easy assumptions about the Middle East, those who governed, and those they governed-the rulers, rebels, and rogues who shaped a region.